2017
DOI: 10.1021/acs.jpca.6b10600
|View full text |Cite
|
Sign up to set email alerts
|

Computational Kinetics by Variational Transition-State Theory with Semiclassical Multidimensional Tunneling: Direct Dynamics Rate Constants for the Abstraction of H from CH3OH by Triplet Oxygen Atoms

Abstract: Rate constants and the product branching ratio for hydrogen abstraction from CHOH by O(P) were computed with multistructural variational transition-state theory including microcanonically optimized multidimensional tunneling. Benchmark calculations of the forward and reverse classical barrier heights and the reaction energetics have been carried out by using coupled cluster theory and multireference calculations to select the most reliable density functional method for direct dynamics computations of the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 103 publications
3
18
0
1
Order By: Relevance
“…Examination of the normal‐mode generalized frequencies along the MEP demonstrated that the slight bump of VaG of R1 is caused by a large decrease in two bending modes of the OCOH group around s = 0.02 a.u. The frequency decreasing in reactive modes sometimes occur because hydrogen abstraction reaction is related to weakening of force constant along the reaction path …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the normal‐mode generalized frequencies along the MEP demonstrated that the slight bump of VaG of R1 is caused by a large decrease in two bending modes of the OCOH group around s = 0.02 a.u. The frequency decreasing in reactive modes sometimes occur because hydrogen abstraction reaction is related to weakening of force constant along the reaction path …”
Section: Resultsmentioning
confidence: 99%
“…This large difference between the TST/Eckart rate constants and those ones computed by Dooley et al could be related to the uncertainties of the thermal kinetics measurements, or the lack of large tunneling corrections in the kinetics model employed since a hydrogen atom is transferred between two heavy atoms, and also due to some known deficiencies on the reactive potential surface built with the B3LYP method …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As tunneling reactivity currently emerges as the third paradigm next to kinetic and thermodynamic control of chemical reactions, it can no longer be ignored. Pertinent recent examples include the conformational preferences of carboxylic acids including amino acids, the reactivity of carbenes, photoreactions, and radical abstractions, to name only a few.…”
Section: Entropy and Nuclear Dynamics Will Be Included Accurately Andmentioning
confidence: 99%
“…Da sich die “Tunnel”‐Reaktivität derzeit als das dritte Paradigma neben der kinetischen und thermodynamischen Kontrolle chemischer Reaktionen entwickelt, kann sie nicht länger ignoriert werden. Als aktuelle Beispiele seien hier die Konformationspräferenzen von Carbonsäuren einschließlich Aminosäuren, die Reaktivität von Carbenen, Photoreaktionen und Radikalabstraktionen genannt.…”
Section: Entropie Und Kerndynamiken Werden Genau Und Routinemäßig Behunclassified